2019
DOI: 10.5539/gjhs.v11n2p55
|View full text |Cite
|
Sign up to set email alerts
|

The Side Effect of Haloperidol in Schizophrenic Patients: Analysis of Red Blood Cell Distribution Width (RDW) and Mean Platelet Volume (MPV) Values

Abstract: INTRODUCTION: Like the increase of pro-inflammatory cytokines and oxidative stress as schizophrenia pathophysiology, haloperidol also increases RDW and MPV values. Both of these values ​​have been clinicians concern because they are a risk factor for the various type of vascular disease. OBJECTIVE: This study aims to determine the side effect of haloperidol on RDW and MPV values in schizophrenic patients. METHODS: This research method uses observational analytic design with a prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Moreover, a case report showed that hemoglobin levels were severely reduced under clozapine and that clozapine-induced anemia originates from bone marrow suppression [ 35 ]. The study by Tanra et al [ 36 ] showed an increase in RDW and mean platelet volume (MPV) under haloperidol, again without differentiation by sex. Iron deficiency anemia, the most common form of anemia, shows a hypochromic, microcytic blood count, whereas the rats in our study are normocytic with decreased hemoglobin levels in male rats like most of the clozapine medicated non-smoker patients [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a case report showed that hemoglobin levels were severely reduced under clozapine and that clozapine-induced anemia originates from bone marrow suppression [ 35 ]. The study by Tanra et al [ 36 ] showed an increase in RDW and mean platelet volume (MPV) under haloperidol, again without differentiation by sex. Iron deficiency anemia, the most common form of anemia, shows a hypochromic, microcytic blood count, whereas the rats in our study are normocytic with decreased hemoglobin levels in male rats like most of the clozapine medicated non-smoker patients [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…10 Moreover, any other factor such as toxic substances, chemotherapeutic agents, radiation, and other drugs impacting the bone marrow stem cells' life cycle, may increase the RDW. [11][12][13] Obesity and metabolic syndrome which are well-known causes of chronic lowgrade systemic inflammation are also associated with higher RDW. 14 Apart from abnormal erythropoiesis, any factor causing RBC fragmentation in peripheral blood could raise the RDW.…”
Section: The Mechanistic Link Between Rdw and Cardiovascular Disordersmentioning
confidence: 99%